Workability Mediates Job Training on Employee Performance (Empiric Study of PT. RKN Forge Indonesia, Karawang District) - Yuliati, Naning; Suherman, Enjang; Anggela, Flora Patricia (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Employee performance is influenced by several things, including the incompetence of employees, which certainly hurts the company. Company efforts in improving performance can be made with job training. This research was conducted to see and determine the effect of job training on work performance which is mediated by the workability of employees. Data analysis used path analysis for verification tests and scale-range analysis to test descriptively, describe all exogenous and endogenous variables and verify hypotheses and the extent of their effects. The sample of respondents in this study is saturated, taking all 77 employees as respondents. This study uses Statistical Product and Service Solutions using path analysis. The test results that have been carried out prove that employee performance and abilities are in the excellent category and job training is in the category according to needs. Meanwhile, employee performance is influenced by training either directly or indirectly by mediating workability. Thus, proper job training will improve workability so that it has a good effect on employee performance.